Self-writing and the decolonial performative scene: urgent narratives, insurgent bodies (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article searched to approach some questions about the different forms of self-writing constructed from memories, testimonies and real documents in the contemporary scene. It was sought to analyze the concepts of autofiction and performativity, aiming to contribute to decolonial discussions by bringing to the center of the scene the knowledge silenced by official history. The discussion focused on the self-fiction scene as a sharing of new urgent narratives and insurgent bodies, making possible an aesthetic and political reflection of the scene. An analysis of two self-fiction shows was carried out as a way to promote new discussions about the decolonial scene.
Keywords: autofiction; performativities; self-writing; decolonial scene